2019
DOI: 10.1002/dc.24253
|View full text |Cite
|
Sign up to set email alerts
|

Improving ROSE: Discrepant touch preparation and histology findings in cytology of renal masses: A 10‐year retrospective review

Abstract: Background The number of “renal incidentalomas” is on the rise due to increasing use of radiologic studies. Image‐guided core needle biopsies (CNB) with touch preparations are performed to guide specimen collection and triage of sample for additional studies. Results allow the clinical team to make appropriate treatment decisions. Design Our electronic database was searched for a 10‐year period to identify 180 image‐guided biopsies of renal masses with rapid on‐site evaluations (ROSE) and corresponding biopsy/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A limited number of studies have examined performance of the ROSE preliminary impression compared with the final diagnosis of renal masses. The diagnostic accuracy of ROSE performed on FNA and/or touch preparations of RMB is reported to be in the range of 85%–95% 43,46–48 . One study examined both FNA and core biopsies with touch preparations and found that ROSE had high sensitivity and positive predictive value (96% and 98.5%, respectively) in adequate specimens for a definitive diagnosis 43 .…”
Section: Pathology: Fna and Core Biopsymentioning
confidence: 99%
See 3 more Smart Citations
“…A limited number of studies have examined performance of the ROSE preliminary impression compared with the final diagnosis of renal masses. The diagnostic accuracy of ROSE performed on FNA and/or touch preparations of RMB is reported to be in the range of 85%–95% 43,46–48 . One study examined both FNA and core biopsies with touch preparations and found that ROSE had high sensitivity and positive predictive value (96% and 98.5%, respectively) in adequate specimens for a definitive diagnosis 43 .…”
Section: Pathology: Fna and Core Biopsymentioning
confidence: 99%
“…The diagnostic accuracy of ROSE performed on FNA and/or touch preparations of RMB is reported to be in the range of 85%-95%. 43,[46][47][48] One study examined both FNA and core biopsies with touch preparations and found that ROSE had high sensitivity and positive predictive value (96% and 98.5%, respectively) in adequate specimens for a definitive diagnosis. 43 Nondiagnostic ROSE was found to have sufficient material to be diagnostic on final diagnosis in 15% of cases.…”
Section: Rapid On-site Evaluationmentioning
confidence: 99%
See 2 more Smart Citations